The Functions of European Criminal Law and the Criminalization Discourse: between the Harm Principle and the Protection of Legal Goods - Cardoso, Raquel (Teisė, 2024)
The aim of this study was to evaluate what the function of European Criminal Law should be, if the national paradigms could be supranationally applied, and, ultimately, to determine the parameters that could confer material legitimacy to the Criminal Law norms of the European Union.